2016
DOI: 10.3390/ijgi5060082
|View full text |Cite
|
Sign up to set email alerts
|

A High-Efficiency Method of Mobile Positioning Based on Commercial Vehicle Operation Data

Abstract: Abstract:Commercial vehicle operation (CVO) has been a popular application of intelligent transportation systems. Location determination and route tracing of an on-board unit (OBU) in a vehicle is an important capability for CVO. However, large location errors from global positioning system (GPS) receivers may occur in cities that shield GPS signals. Therefore, a highly efficient mobile positioning method is proposed based on the collection and analysis of the cellular network signals of CVO data. Parallel-and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 31 publications
(30 reference statements)
0
14
0
Order By: Relevance
“…This is based on mathematical principles, and can be categorized as descriptive statistics and inferential statistics [5][6][7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is based on mathematical principles, and can be categorized as descriptive statistics and inferential statistics [5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…(2) Data cleaning Planting area x 4 Air temperature x 5 Cost of production x 6 Market trading price Y Total harvest (…”
Section: ) Data Integrationmentioning
confidence: 99%
“…However, these techniques may no longer be applicable if the problems of multi-path propagation of wireless signals exist [13]. The study indicated that the availability of GPS may be lower in urban roads, and the GPS modules may be invalid [9]. Furthermore, higher power consumption is required by these techniques [1].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, higher power consumption is required by these techniques [1]. Therefore, some studies proposed cellular-based positioning methods to analyze the signals of cellular networks for reliably estimating the locations of mobile stations [1,5,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, higher power consumptions are required by these techniques [1]. Therefore, some studies proposed cellular-based positioning methods to analyze the signals of cellular networks for location estimation [1, 6,8,11,13,14]. Although cellular-based positioning methods can estimate the locations of mobile stations without GPS modules, big errors of estimated locations may be obtained.…”
Section: Introductionmentioning
confidence: 99%